The Art Ecosystem of Amreta ing Huma - I Gusti Ngurah Diva Ismayana; I Wayan Mudra; I Ketut Sariada (Journal of Aesthetics, Creativity and Art Management, 2026)
Amreta ing Huma is an art ecosystem whose ideas sparked the subak phenomenon and its current existence. By linking culture, society, education, politics, technology, economics, and stakeholders, it can become an alternative way of thinking for Balinese society, both nationally and internationally. This paper is compiled based on the results of fieldwork through a qualitative approach, namely the implementation of interview methods accompanied by direct observation, the process of transcribing information in the form of field data, processing data to compiling data into a systematic and coherent data report. The aesthetic approach used is that of Clive Bell and William Morris, along with a sustainable ecological art approach. Amreta ing Huma, interpreted as the water of life in rice fields, is a product of thought in the form of an art ecosystem. The achievement of an art ecosystem begins with the creation of the Amreta ing Huma artwork, ecological art, which ultimately forms an art ecosystem. Based on this artwork, a role model for interaction within the community is established through the perspectives of culture, education, politics, economics, and stakeholders.